Optimization of phorotannins extraction and evaluation of antioxidant and anti-inflammatory properties of Fucus vesiculosus - Amarante, Sónia de Jesus (2019)
Phlorotannins, a class of polyphenols exclusive to brown seaweeds, have been associated with numerous health-promoting properties. In this, the objective of the master's thesis was to optimize the extration process of phlorotannins from the seaweed Fucus vesiculosus, using microwave-assisted extraction methodology and a green solvent, such as ethanol, as well as to characterize the constituents of the obtained extracts and to realize its biological potentialities. The optimization of the microwave extraction process was performed by singlefactor analysis followed by Box-Behnken analysis, considering the maximum recovery of phlorotannins, yielding a maximum of 3.16 ± 0.17 mg phloroglucinol equivalents/g dry weightalgae. The crude extract obtained was partitioned and the resulting fractions, n-hexane (Hex), ethyl acetate (EtOAc) and aqueous (Aq), were characterized by UHPLC-DAD-ESI/MS. Both crude extract and purified fractions were screened for antioxidant capacity by in chemico assays. Additionally, fractions with better antioxidant capacity, namely EtOAc and Hex, were tested on lipopolysaccharide-stimulated RAW 267.4 macrophages. The chemical analysis of the purified fractions allowed to identify some phlorotannins, mainly in EtOAc and Aq. On the other hand, the Hex fraction was rich in fucoxanthin, which along with other pigments, was also present in the EtOAc fraction. Overall, the EtOAc and Hex fractions were shown to be most effective regarding the antiradical capacity, and in particular against the nitric oxide radical. Both these fractions reduced significantly the nitrite levels produced by activated macrophages without causing a decrease in their cellular metabolism. In addition they were able to downregulate the inflammationmediating enzyme iNOS and, particularly EtOAc reduced the levels of COX-2. It is possible that these facts can be related with the transcriptional factor NF-kB, since the expression of p65 subunit was significantly decreased in the cellular lysates of the pre-treated macrophages, followed by the inhibition of p-IkB-α phosphorylation. Taken together, the findings from the present dissertation suggest that EtOAc and Hex fractions of F. vesiculosus have relevant antioxidant and anti-inflammatory activities.